Carcinogen‐induced tumors in SFN‐transgenic mice harbor a characteristic mutation spectrum of human lung adenocarcinoma. Issue 8 (23rd July 2019) - Kim, Yunjung; Shiba‐Ishii, Aya; Ramirez, Karina; Muratani, Masafumi; Sakamoto, Noriaki; Iijima, Tatsuo; Noguchi, Masayuki
Abstract: The landscape of genetic alterations in disease models such as transgenic mice or mice with carcinogen‐induced tumors has provided a huge amount of information that has shed light on the process of tumorigenesis in human non‐small‐cell lung cancer (NSCLC). We have previously identified stratifin ( SFN ) as a potent oncogene, and generated SFN ‐transgenic (Tg‐SPC‐SFN +/− ) mice, which express human SFN (hSFN) only in the lung. Here, we have found that carcinogen nicotine‐derived nitrosaminoketone (NNK)‐induced tumors developing in Tg‐SPC‐SFN +/− mice show a similar histology to human lung adenocarcinoma and exhibit high hSFN expression. In order to compare the genetic characteristics of Tg‐SPC‐SFN +/− tumors and human lung adenocarcinoma, the former were subjected to whole‐exome sequencing. Interestingly, Tg‐SPC‐SFN +/− tumors showed the distinct distribution of exonic mutations and high number of mutated genes and transversion. Moreover, Tg‐SPC‐SFN +/− tumors showed 73 genes that were commonly detected in more than 2 tumors, mutations of which were also found in human lung adenocarcinoma. The expression levels of some of these genes were significantly associated with the clinical outcome of lung adenocarcinoma patients. Additionally, mutated genes in Tg‐SPC‐SFN +/− tumors were closely associated with key canonical pathways such as PI3K/AKT signaling and apoptosis signaling. These results suggest that SFN overexpression is a universal abnormality in human lung adenocarcinogenesis and Tg‐SPC‐SFN +/− tumors recapitulate key features of major human lung adenocarcinoma. Therefore, Tg‐SPC‐SFN +/− mice provide a useful model for clarifying the molecular mechanism underlying lung adenocarcinogenesis. Abstract : In this study, we identified 73 common mutated genes among 4 Tg‐SPC‐SFN +/− tumors, which were predicted to be associated with tumorigenesis. The expression levels of some of these genes were significantly associated with the clinical outcome of lung adenocarcinoma patients. Therefore, we suggest that Tg‐SPC‐SFN +/− tumors recapitulate key features of major human lung adenocarcinoma.